A Case of Ricocheted Gun Shot Injury - Gurmeet Singh Sarla (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2020)
Ricocheted bullets may hold adequate kinetic energy to cause gunshot wounds. This arrangement of pictures presents an instance of ricochet gunshot injury and talks about the attributes of ricochet entrance wounds and wound tracks, taking note of significant contemplations for appraisal of a potential ricochet occurrence.